Lesion stiffness measured by shear-wave elastography: Preoperative predictor of the histologic underestimation of US-guided core needle breast biopsy. Issue 12 (December 2015) - Park, Ah Young; Son, Eun Ju; Kim, Jeong-Ah; Han, Kyunghwa; Youk, Ji Hyun
Abstract: Objectives: To determine whether lesion stiffness measured by shear-wave elastography (SWE) can be used to predict the histologic underestimation of ultrasound (US)-guided 14-gauge core needle biopsy (CNB) for breast masses. Methods: This retrospective study enrolled 99 breast masses from 93 patients, including 40 high-risk lesions and 59 ductal carcinoma in situ (DCIS), which were diagnosed by US-guided 14-gauge CNB. SWE was performed for all breast masses to measure quantitative elasticity values before US-guided CNB. To identify the preoperative factors associated with histologic underestimation, patients' age, symptoms, lesion size, B-mode US findings, and quantitative SWE parameters were compared according to the histologic upgrade after surgery using the chi-square test, Fisher's exact test, or independent t -test. The independent factors for predicting histologic upgrade were evaluated using multivariate logistic regression analysis. Results: The underestimation rate was 28.3% (28/99) in total, 25.0% (10/40) in high-risk lesions, and 30.5% (18/59) in DCIS. All elasticity values of the upgrade group were significantly higher than those of the non-upgrade group ( P  < 0.001). On multivariate analysis, the mean (Odds ratio [OR] = 1.021, P  = 0.001), maximum (OR = 1.015, P  = 0.008), and minimum (OR = 1.028, P  = 0.001) elasticity values were independently associated with histologic underestimation. The patients' age, lesion size, and final assessment category on US of the upgrade group were higher than those of the non-upgrade group ( P  = 0.046 for age; P  = 0.021 for lesion size; P  = 0.030 for US category), but these were not independent predictors of histologic underestimation on multivariate analysis. Conclusion: Breast lesion stiffness quantitatively measured by SWE could be helpful to predict the underestimation of malignancy in US-guided 14-gauge CNB.